CASE REPORT: AN ASCARIASIS CASE IN A MALE KIDS ON SEMARANG - Zulaikhah, Siti Thomas (JURNAL KEDOKTERAN RAFLESIA, 2021)
Soil-transmitted Helminths (STH) often cause slightly high numbers of comorbids, especially in developing countries. Ascaris lumbricoides is the STH that most often causes infection, which is called Ascariasis. The high rate of STH infection is caused by poor environmental sanitation and poor habits of Clean and Healthy Lifestyle (PHBS) of the population. In Indonesia, STH infection is one of the main public health problems with prevalence ranged between 45% to 65%. Indeed the prevalence can reach 80% in areas with poor sanitation. The high prevalence of helminthiasis cases in Indonesia, especially in the work area of the Pusekesmas Bangetayu Semarang, the authors are interested in further exploring the diarrhea case in An. AR at Pusekesmas Bangetayu Semarang with an epidemiological triangle approach